ANALISA TEORITIS HASIL PENGENDALIAN KOROSI PADA INSTALASI PIPA MINYAK DI PERUSAHAAN X - Tierza Yulia Waworundeng; Samuel M. J. S. Tuny; Berthy Pelasula (Department of Mechanical Engineering, 2024)
Corrosion in oil pipelines is a frequent problem in the upstream oil and gas industry, reducing the strength of the structure to withstand fluid pressure and causing severe damage that cannot be repaired. This study aims to determine the factors that cause corrosion, apply the coating method as corrosion control, and conduct a comparative analysis of the corrosion control methods used in the oil piping system. The results of the analysis show that environmental conditions affect the type of material to be used. The use of the right pipe material such as stainless steel or API 5L steel can help in the selection of corrosion control methods, one of which is the coating method. Thus, this research helps to improve the operational efficiency of oil pipeline installations, reduce damage, and extend the service life of pipelines. In addition, this study also aims to compare the effectiveness of the corrosion control methods applied and the materials used, so that it can provide the right recommendations to control corrosion in oil pipes using an effective coating method.